Pembudidayaan Tanaman Hortikultura Dengan Metode Green House - Sukur Abdurahman; Amanda Ayu Ningtyas; Angelica Raulima; Mey Linda Airiyani; Muhammad Yaskur Nasir; Muhammad Syarifudin; Muhammad Ilham Aditya Nugraha (xxxx-xxxx, 2023)
Abdurahman S, Ningtyas AA, Raulima A, Airiyani ML, Nasir MY, Syarifudin M, Nugraha MIA.  2022. Horticultural cultivation with the green house method. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 283-292. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Horticultural crops with the green house method can be carried out in a controlled manner in the cultivation process and help overcome the narrowing of agricultural land. This survey aimed to find out how to cultivate and what types of horticultural plants can be grown using the green house method. The research method is carried out by means of surveys and interviews with green house owners by paying attention to the components in making green houses starting from seeds, cultivation and harvest yields. Green houses can protect plants from plant pests that come from outside without blocking the entry of light. The arrangement of horticultural plants based on their types can add an element of beauty so that they can be used as new tourist attractions. The use of greenhouses for horticultural crops is a solution to the limited land area for growing various types of plants, both vegetables and others, as well as developing contextual media. The use of green houses in plant cultivation is one way to provide a more accessible environment for optimum position conditions for plant growth. So with the application of horticultural cultivation with the green house method, it is able to facilitate farmers in the cultivation process, especially in land use, overcoming pests and maintaining air humidity. The use of green houses in plant cultivation is one way to provide a more accessible environment to obtain optimum conditions for plant growth.